The Insertion of Milton Santos’ Geographic Space in the Althusserian Interpretation of the Social Whole: A Structure Like the Others? - Costa, Bruno Moreira Riani [UNESP] (Universidade de São Paulo, 2023)
The present article intends to investigate some of the possible theoretical approximations between Santos’ propositions about geographic space and the Althusserian interpretation. Mainly, the discussion revolves around the following question: How far could one go by reading certain propositions by Milton Santos through the lens of structural Marxism? It is concluded that, as a necessary support for the historicization of social structures, space assumes unique importance for the analysis of reality through an Althusserian prism: its consideration suggests a forwarding of the contradiction between history and structure, allowing to contemplate the diachrony and contradiction present in each socio-spatial formation. Thus, just as the analysis of the Althusserian ballast of certain elaborations by Milton Santos helps to illuminate certain points of his work, Santos’ work can also contribute largely to the theorizations of structural Marxism, highlighting the role of space in the construction of an analytical framework capable of unravelling the determinations of the present.

Este artículo pretende investigar algunas de las posibles afinidades teóricas entre las proposiciones de Santos sobre el espacio geográfico y el esquema interpretativo althusseriano. Principalmente, la discusión gira en torno a la siguiente pregunta: ¿hasta dónde se puede llegar al emprender una lectura de ciertas proposiciones de Milton Santos a través de la lente del marxismo estructural? Se llega a la conclusión de que, como soporte necesario para la historización de las estructuras sociales, el espacio adquiere una importancia única para el análisis de la realidad: su consideración sugiere abordar la contradicción entre historia y estructura, permitiendo la contemplación de la diacronía y contradicción presente en cada formación socioespacial. De esta forma, así como el análisis de la inspiración althusseriana de ciertas elaboraciones de Milton Santos ayuda a iluminar ciertos puntos de su obra, la obra de Santos también puede contribuir en gran medida a las teorizaciones del marxismo estructural, destacando el papel del espacio en la construcción de un marco analítico capaz de desentrañar las determinaciones del presente.
La inserción del espacio geográfico de Milton Santos en la matriz de interpretación althusseriana de la totalidad social: ¿una estructura como las demás?
Keywords: geographic space; social structure; Milton Santos